Ijtihad 'Izzuddin Bin Abdussalam about Bid'ah and Its Relevance to Local Wisdom in Indonesia - Muchlis Bahar (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
This paper aims to analyze the ijtihad of 'Izzuddin Bin Abdussalam regarding Bid'ah and its relevance to the practice of religious life of the Islamic community in Indonesia associated with local wisdom. This research is a qualitative descriptive study, the primary source is the book Qawa'idul Ahkam Fi Mashalihil-Anam, with a local wisdom concept approach. Secondary sources are other books related to the discussion of local wisdom. The religious practices of the Muslim community in Indonesia, such as the tradition of reading the surah Yasin, Tahlilan, the commemoration of the Prophet's Birthday, dzikir collectively, were analyzed with the classification of bid'ah according to 'Izzuddin bin Abdis salam. The findings of this study are that the religious practices of Indonesian Muslims such as yasinan, tahlilan and dzikir collectively can be included in the category of permissible bid'ah (mubahah). This means that it is a good tradition, which is allowed because it is a good culture of the Indonesian people or can be referred to as al-Urf al-Sahih. This opinion is in accordance with the local wisdom of the Indonesian people who generally follow the Shafi'iyah school, relevant to the notion of religious moderation which prioritizes religious moderation, tolerance, and moderate attitude (washaty).